2021
DOI: 10.14812/cuefd.865337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flipped Learning Model on Primary and Secondary School Students' Mathematics Achievement: A Meta-Analysis Study

Abstract: With the transition to distance education during the coronavirus pandemic, one of the most talked about teaching approaches has been the flipped learning model (FLM).Conducting the discussions about FLM on a solid basis can only be achieved by finding an answer to what the effect of FLM has in different fields and different education levels. Based on this idea, in this study, it is aimed to evaluate the results of the studies examining the effect of FLM on the mathematics achievement of primary and secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(85 reference statements)
4
7
0
1
Order By: Relevance
“…As another moderator of this study, different educational levels do not have different impact on students' academic achievements (p=840). This finding was also reported by Orhan (2019), Lag and Saele (2019) and Alten et al (2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As another moderator of this study, different educational levels do not have different impact on students' academic achievements (p=840). This finding was also reported by Orhan (2019), Lag and Saele (2019) and Alten et al (2019).…”
Section: Discussionsupporting
confidence: 88%
“…Shahnama, Ghonsooly and Shirvan (2021) also concluded that flipped learning has large and positive effect on EFL/ESL student's success through a meta-analysis including 69 studies. Moreover, meta-analysis studies conducted in different areas to examine the effect of flipped learning on academic achievements found similar results (Orhan, 2019;Aydın et al, 2020;Hew & Lo, 2018).…”
Section: Discussionmentioning
confidence: 56%
“…Flipped classroom uses a revised version of Bloom's taxonomy as an inverted form for cognitive objectives. Applying and analyzing take the role of remembering and learning, which are the main activities in a traditional classroom, as seen in Figure 1 ( Gariou-Papalexiou et al, 2017;Yildirim Yakar, 2021).…”
Section: Benefits Of Flipped Classroommentioning
confidence: 99%
“…Alper ve Öztürk (2018) yaptıkları çalışmada akademik başarılarını, uygulanan ters yüz öğrenme modeli ile arttırdığını belirlemişlerdir. Yıldırım Yakar (2021) tarafından ters yüz öğrenme modelinin ilk ve ortaöğretim öğrencilerinin matematik başarısına etkisini belirlemek amacıyla yapılan araştırmada öğrencilerin başarılarının arttığını orta öğretimde daha etkili olduğunu belirlemiştir. Güç (2017) ters yüz sınıf yöntemini kullanarak ortaokul yedinci sınıf öğrencilerinin matematik dersinde başarılarını arttırdığını belirlemiştir.…”
Section: Tartişma Ve Sonuçunclassified